Terrestrial organic matter input suppresses biomass production in lake ecosystems - Karlsson, Jan (2015)
Terrestrial ecosystems export large amounts of organic carbon (t-OC) but the net effect of thisOC on the productivity of recipient aquatic ecosystems is largely unknown. In this study ofboreal lakes we show that the relative contribution of t-OC to individual top consumer (fish)biomass production, and to most of their potential prey organisms, increased with theconcentration of dissolved organic carbon (DOC; dominated by t-OC sources) in water.However, the biomass and production of top consumers decreased with increasingconcentration of DOC, despite their substantial use (up to 60%) of t-OC. Thus, the resultssuggest that although t-OC supports individual consumer growth in lakes to a large extent, tOCinput suppresses rather than subsidizes population biomass production.